PENGARUH KEPEMIMPINAN DAN DUKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN PENDAPATAN DAN ASET DAERAH KABUPATEN NIAS SELATAN - Josep Sastria Daya (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
At the Financial Management Agency for Revenue and Regional Assets of South Nias Regency, the scope of this study is to ascertain how employee performance is affected by leadership and organizational support in part and simultaneously. Quantitative research is the method of choice. All 45 employees of the Financial Management Agency for Revenue and Regional Assets of South Nias Regency make up the population and sample. Multiple linear regression analysis is used for the data analysis. The study's t-value for leadership is 3.046>t-table 1.682, and the significance level is 0.004 0.005. Additionally, the significance level for organizational support is 0.000 0.005, and the t-value is 9.819> t-table 1.682. According to the findings of this study, it is necessary to verbally warn employees who are absent consecutively for three days in order to improve employee performance and achieve goals. Pioneers need to give inspiration to representatives who have functioned admirably.